Roles of Cooperatives in Fish Farming Development in Chitwan and Nawalparasi Susta East Districts - Rajthala, Sabina; Rai, Sunila; Jha, Dilip K.; Bista, Jay Dev; Avento, Roseanna (Our Nature, 2020)
A study was conducted to assess the role of cooperatives in improving fish farming through a comparison of fish farmers engaged and not engaged in cooperatives. Altogether, 140 fish farmers were selected from Chitwan and Nawalparasi Susta East district, 70 from each district. Annual income from fish production and annual total income was found significantly higher (p<0.05) in non-cooperative fish farmers than cooperative fish farmers in Nawalparasi Susta East. The latter district has more fish farmers that have large-scale commercial operations. Fish farmers in cooperatives are mostly small-holders, whose production is consumed domestically. Non-cooperative fish farmers faced more (P>0.05) challenges than cooperative farmers especially in terms of seed quality and quantity. Cooperatives were attractive for their support in saving and micro-finance schemes. The study advocates for increased support to establishment of cooperatives as they have great potential to develop fish farming sustainably and to empower their members socially and economically.